THE EFFECTIVENESS OF CPR VIDEO FOR LAY COMMUNITIES ABILITY IN CONDUCTING CPR IN SEMBUNG VILLAGE OF NARMADA DISTRICT - A’an Dwi Sentana; Gusti Ayu Sri Puja Warnis Wijayanti; Ni Putu Sumartini (poltekkes kemenkes mataram, 2018)
Abstract: The efforts to improve the ability for lay people in conducting Cardiopulmonary Resucitation (CPR) need to be done. One of them is to provide CPR training using CPR video. The purpose of this study is to determine the effect of CPR video to improve the ability for lay people in conducting CPR. Research design was Quasi experiment with pretest posttest group with the population was the lay communities in Sembung village, Narmada district. Sampling that would be used by researcher was purposive sampling, with a number of sample was 30 belong to treatment group and 30 of control group.The results showed Wilcoxon Signed Ranks Test statistic for the treatment group on Knowledge p value (0.000) ≤ 0.05 control group p value (0.000) ≤ 0.05. The attitude of the treatment group p value (0.000) ≤ 0.05, control group value p (0.467)> 0.05. The action on the treatment group p value (0.000) ≤ 0.05, in the control group p value (0.000) ≤ 0.05. Mann Whitney U Test Result Test Mann-Whitney U Test that knowledge on treatment and control group p value (0,514)> 0,05 while attitude with p value (0,049) ≤ 0,05 and action with value p (0,000) ≤ 0, 05. To improve the ability of communities to participate in the training can utilize a learning media such as CPR video. It is expected can guide the communities in doing CPR properly. Keywords: CPR Video, Communities ability.